Induction of Severe Eosinophilic Esophagitis and Multi-Organ Inflammation by Airborne Allergens is Associated with IL-4/IL-13 and CCL11 but Not IgE in Genetic Susceptible Mice - Maskey A; Srivastava K; Soffer G; Dunkin D; Yuan Q; Li XM (Dove Medical Press, 2022)
Anish Maskey,1 Kamal Srivastava,1,2 Gary Soffer,3 David Dunkin,4 Qian Yuan,5 Xiu-Min Li1,6 1Department of Pathology, Microbiology & Immunology, New York Medical College, Valhalla, NY, USA; 2General Nutraceutical Technology, LLC, Elmsford, NY, USA; 3Department of Allergy and Immunology, Yale University, New Haven, CT, USA; 4Division of Pediatric Gastroenterology and Mindich Child Health and Development Institute, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 5Pediatric Gastroenterology and Nutrition, Mass General Hospital for Children, Boston, MA, USA; 6Department of Otolaryngology, New York Medical College, Valhalla, NY, USACorrespondence: Xiu-Min Li, Department of Pathology, Microbiology & Immunology, New York Medical College, 40 sunshine cottage Road, BSB 319, Valhalla, NY, 10595, USA, Tel +1-914-594-4197, Email XiuMin_Li@nymc.eduBackground: Eosinophilic Esophagitis (EoE) is an increasingly common chronic inflammatory disease. The pathological mechanisms underlying EoE are largely unknown.Objective: We sought to understand the mechanisms underlying aeroallergen-induced EoE in Sharpin gene deficient (Sharpin-/-) mice that is prone to inflammatory response.Methods: Sharpin-/-mice were exposed with Aspergillus fumigatus and ovalbumin intranasally every alternate day for 4 weeks. Wild type (WT) naïve mice, WT exposed, and un-exposed Sharpin-/- mice were controls. Histopathological analysis was performed by H&E, trichrome and major basic protein staining. Total and specific IgE, IgG, and IgA levels were measured by ELISA and Th2 cytokine and CCL11 chemokine gene expression were determined.Results: Airborne allergen exposed Sharpin-/- mice showed severe eosinophilic inflammation in the esophagus (p < 0.001), and markedly increased epithelial thickening (p < 0.0001) compared to WT normal controls, whereas airborne allergen exposed WT mice and unexposed Sharpin-/- mice only showed mild eosinophilic inflammation in the esophagus. These exposed Sharpin-/- mice also showed over 7-fold increase in blood eosinophils (p < 0.0001), 60-fold increase in eosinophils in bronchoalveolar lavage fluid (p < 0.0001) and 4-fold increase in eosinophils in the skin (p < 0.0001) compared to normal controls. Surprisingly, exposed Sharpin-/- mice did not show elevation of serum total or antigen-specific IgE levels but reduced total IgA and IgG levels than normal controls There was a marked increase in IL-4, IL-13 and CCL11 gene expression in esophageal tissue (p < 0.001) in exposed Sharpin-/- mice compared to WT normal mice.Conclusion: Th2 cytokines and chemokines, but not IgE may play an important pathologic role in aeroallergen-induced EoE. This study may provide insight into new therapeutics for EoE.Keywords: aeroallergen, eosinophilic esophagitis, non-IgE, Th2